Efficacy of a medical device based on magnesium alginate, calcium carbonate, potassium bicarbonate, sodium hyaluronate and chondroitin sulfate in the adjuvant treatment of non-erosive gastroesophageal reflux disease (NERD) - Sgarbi, Daniela; Nicita, Rinaldo Carmelo (Archives of Clinical and Biomedical Research, 2025)
Treatment of non-erosive gastroesophageal reflux disease (NERD) is based on the use of proton pump inhibitors (PPIs), but clinical experience shows that patients with NERD often complain of dissatisfaction with PPI monotherapy and with their health-related quality of life. Hence, the need to identify effective alternative therapeutic actions emerges. This retrospective pilot study was carried out on 66 subjects divided into two groups: 33 patients with NERD took a medical device (MD) containing magnesium alginate, calcium carbonate, potassium bicarbonate, sodium hyaluronate and chondroitin sulfate for 60 consecutive days, while the other 33 patients with NERD concomitantly took a PPI and the aforementioned medical device for 60 consecutive days. The medical device was taken after the main meals and before bedtime. Symptoms were assessed using the Gastroesophageal Reflux Disease Impact Scale (GIS) questionnaire and reflux-related quality of life using the Gastroesophageal Reflux Disease- Health Related Quality of Life (GERD-HRQL) questionnaire before starting treatment, after 30 days of treatment, at the end of 60 days of treatment and 30 days after the discontinuation of the treatment. Patients in both groups showed a clinically significant improvement. In particular, after 30 days of therapy, the mean percentage reduction of the total GIS score compared to T0 was 50.1% in the MD Group and 46.7% in the MD+PPI Group. After 60 days of therapy, the mean percentage reduction of the total GIS score compared to T0 was 55.5% in the MD Group and 53.9% in the MD+PPI Group. The benefits obtained by patients in both groups resulted in a significant improvement in the reflux-related quality of life, which was confirmed by the significant reduction in the GERD-HRQL questionnaire score. The results obtained in the two groups were superimposable, demonstrating that in the analyzed sample of patients with NERD, therapy with the medical device alone yielded the same therapeutic effects as the combination therapy with PPI and medical device.